1999
DOI: 10.1159/000018693
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colorectal Surgery:A Five-Year Experience

Abstract: Objective: The aim of this study was to assess the feasibility and outcome of 300 laparoscopic colorectal procedures performed within 5 years for both benign and malignant disorders. The specific purpose was to identify the impact of the learning curve on reducing morbidity and on improving the outcome of laparoscopic colorectal surgery. Patients and Methods: All cases were divided into 3 groups: the first 100, the second 100 and the third 100 procedures were analyzed. Statistical analysis was performed by Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 53 publications
3
23
0
10
Order By: Relevance
“…The rate of conversion to open surgery is low when strict eligibility criteria are applied and the surgical team is well trained. 16 The highest conversion rates were reported in series resulting from early experiences. [17][18] Data from our study indicate that extent of resection including proximal, distal and CRM margins and lymph node examination were similar in both rectal resection groups.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of conversion to open surgery is low when strict eligibility criteria are applied and the surgical team is well trained. 16 The highest conversion rates were reported in series resulting from early experiences. [17][18] Data from our study indicate that extent of resection including proximal, distal and CRM margins and lymph node examination were similar in both rectal resection groups.…”
Section: Discussionmentioning
confidence: 99%
“…When dividing the groups of two most frequent surgical procedures into subgroups with the first half of surgeries (subgroup 1) and the second half of surgeries (subgroup 2), we observed reduced mean duration of surgery and reduced rate of conversions. In the study conducted by Bruch et al 15 , the learning curve in laparoscopic colorectal surgery was analyzed by dividing 300 patients into 3 groups of 100, for the period of 5 years. Conversion was observed in 22 cases (7.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Pricolo and Potenti [17]in their review concluded that the mainstay of treatment remains surgical despite use of adjuvant therapy. In addition, other authors have shown good results for colorectal cancer operated laparoscopically without pre-operative adjuvant therapy [18]. …”
Section: Discussionmentioning
confidence: 99%